2020
DOI: 10.1007/s00018-020-03498-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and circuit mechanisms regulating cocaine memory

Abstract: Risk of relapse is a major challenge in the treatment of substance use disorders. Several types of learning and memory mechanisms are involved in substance use and have implications for relapse. Associative memories form between the effects of drugs and the surrounding environmental stimuli, and exposure to these stimuli during abstinence causes stress and triggers drug craving, which can lead to relapse. Understanding the neural underpinnings of how these associations are formed and maintained will inform fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 212 publications
(380 reference statements)
0
19
0
Order By: Relevance
“…Learning and memory processes associate memories between cocaine’s reinforcing and rewarding effects and environmental stimuli, which then will trigger cocaine craving during abstinence. This vulnerability to relapse, even after a long period of abstinence, involves stable gene expression changes and epigenetic modifications, especially in the corticostriatolimbic circuitry (hippocampus, prefrontal cortex, NAc, dorsal striatum, and amygdala) [ 17 ]. Stress plays an important role in relapse since increases drug craving, involving mainly the HPA axis and corticotropin-releasing factor [ 18 ].…”
Section: Neurobiologymentioning
confidence: 99%
“…Learning and memory processes associate memories between cocaine’s reinforcing and rewarding effects and environmental stimuli, which then will trigger cocaine craving during abstinence. This vulnerability to relapse, even after a long period of abstinence, involves stable gene expression changes and epigenetic modifications, especially in the corticostriatolimbic circuitry (hippocampus, prefrontal cortex, NAc, dorsal striatum, and amygdala) [ 17 ]. Stress plays an important role in relapse since increases drug craving, involving mainly the HPA axis and corticotropin-releasing factor [ 18 ].…”
Section: Neurobiologymentioning
confidence: 99%
“…Acetylation and deacetylation of chromatin is another signaling pathway involved in regulating the formation of drug context-associated memories contributing to addiction-like behaviors (Rogge et al, 2013;Bender and Torregrossa, 2020;Campbell et al, 2021). These processes are regulated by two kinds of functionally similar enzymes.…”
Section: Function Of Epigenetic Mechanisms In Preventing Drug Relapsementioning
confidence: 99%
“…Thus, relapse prevention is a particularly important goal for treatment. Long-lasting drug-associated memory formation is closely associated with the rewarding effects of the drug and drug exposure context (Bender and Torregrossa, 2020). Accumulating preclinical studies have also suggested that exposure to drug-associated contextual stimuli may reactivate drug-associated memories, evoke craving, and promote drug relapse in drug addicts (Farrell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%